TGH. M. Zainuddin, AM: Tuan Guru Abad XX yang Paling Berpengaruh Dalam Masyarakat Sasak - Jamaluddin, Jamaluddin (Alif Lam : Journal of Islamic Studies and Humanities, 2023)
TGH. M. Zainuddin Abdul Majid is a highly respected figure, both in the fields of education, politics, the general public, and military affairs, as well as in the realm of peer-to-peer cooperation. This article will discuss how TGH. M. Zainuddin Abdul Majid became the most influential person in the Sasak community. Since many of the articles in this series use statistical data, the statistical derivation that is used is the statistical derivation. This text confirms that TGH. M. Zainuddin Abdul Madjid succeeded in becoming the most influential person in the Sasak community. This is demonstrated by the following: first, a large number of madrasahs and mesjids built in the pulau Lombok; second, a large number of Tuan Gurus who are Muslim scholars who teach the Islamic teachings of Ahlussunnah wal Jamaah; and third, a large number of Sasak people who identify as Muslim women who live in the desa-desa of Lombok.